Fostering the Learners' Arabic Speaking Skills through the Talking Stick Technique - Kamal, Helmi; Takwim, Mardi; Amrulloh, Muhammad Afif; Habibi, Burhan Yusuf (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
This research aimed to determine whether the talking stick technique fosters the learners' Arabic speaking skills. The research design used a quasi-experimental method. The participants of this research were the eleventh graders of Madrasah Aliyah Negeri Palopo, consisting of 40 learners. The sampling technique was purposive sampling. The research instrument was an oral test. The writer conducted the test for learners before and after the treatments. The research results show a significant improvement in the learners' speaking skills using the talking stick technique. The average score of the last test for the experimental group was higher than the controlled group (74.70 > 56.55), and the standard deviation for the experimental group was 8.355 and for the controlled group was 15.753. Meanwhile, the probability value was lower than alpha (0.000 < 0.05). The null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. This research is hoped to benefit the development of Arabic language teaching.